INOVASI KURIKULUM PAI SEBAGAI PROGRAM DERADIKALISASI - Ayub Bahrudin; Sri Wahyuni; Tasara Amida Ardian Sari; Yusuf Arsyad Wahid Tajuddin; Zakiyyatur Rohmah (At-Tarbiyat, 2020)
Radical action is a serious problem facing the Indonesian people. This case cannot be separated from the lack of public attention to religious education Coupled with the role of the government which pays little attention to the Islamic Religious Education system for schools in Indonesia. Islamic Education that fosters moderate character can be a solution to this problem. Therefore the purpose of this study is to explain how Islamic Religious Education plays a role in deradicalization and how PAI's curriculum innovations can produce people of moderate character. This research is a literature research using content analysis. The conclusion of this research is that first, Islamic Education can play a role in deradicalization through material content, the Teacher's thinking style and teacher's guidance to students. Secondly, curriculum innovation to form moderate character can be done by giving a load of tolerance values ​​and patriotism, creating teachers with an inclusive paradigm, implementing learning in a creative and actual way.